Estimation of monthly global solar radiation from sunshine duration measurement in Elazig - Togrul, IT; Togrul, H; Evin, D (Pergamon-Elsevier Science Ltd, 2000)
In this study, the relation between a and b terms and (n) over bar/(N) over bar was investigated to estimate the global solar radiation in Elazig by using different regression analyses. Equations which contain the whole year and two different periods, winter and summer, were developed. Eqs, (5)-(7) which represent second, third and fourth degree equations respectively, gave the best results in all of the equations having an error less than 1%. Contrary to expectations, the equations developed for summer and winter periods had higher errors than the others. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: estimation of solar radiation; Angstrom constants; sunshine duration